Long-term survival with IDH wildtype glioblastoma: first results from the ETERNITY Brain Tumor Funders' Collaborative Consortium (EORTC 1419) - Hertler, Caroline; Felsberg, Jörg; Gramatzki, Dorothee; Le Rhun, Emilie; Clarke, Jennifer; Soffietti, Riccardo; Wick, Wolfgang; Chinot, Olivier; Ducray, François; Roth, Patrick; McDonald, Kerrie; Hau, Peter; et al. (European journal of cancer, 2023)
BACKGROUND: Median survival with glioblastoma remains in the range of 12 months on population levels. Only few patients survive for more than 5 years. Patient and disease features associated with long-term survival remain poorly defined. METHODS: European Organization for Research and Treatment of Cancer (EORTC) 1419 (ETERNITY) is a registry study supported by the Brain Tumor Funders Collaborative in the US and the EORTC Brain Tumor Group. Patients with glioblastoma surviving at least 5 years from diagnosis were identified at 24 sites in Europe, US, and Australia. In patients with isocitrate dehydrogenase (IDH) wildtype tumours, prognostic factors were analysed using the Kaplan-Meier method and the Cox proportional hazards model. A population-based reference cohort was obtained from the Cantonal cancer registry Zürich. RESULTS: At the database lock of July 2020, 280 patients with histologically centrally confirmed glioblastoma (189 IDH wildtype, 80 IDH mutant, 11 incompletely characterised) had been registered. In the IDH wildtype population, median age was 56 years (range 24-78 years), 96 patients (50.8%) were female, 139 patients (74.3%) had tumours with O6-methylguanine DNA methyltransferase (MGMT) promoter methylation. Median overall survival was 9.9 years (95% confidence interval [95% CI] 7.9-11.9). Patients without recurrence experienced longer median survival (not reached) than patients with one or more recurrences (8.92 years) (p < 0.001) and had a high rate (48.8%) of MGMT promoter-unmethylated tumours. CONCLUSIONS: Freedom from progression is a powerful predictor of overall survival in long-term survivors with glioblastoma. Patients without relapse often have MGMT promoter-unmethylated glioblastoma and may represent a distinct subtype of glioblastoma.
Gesehen am 18.06.2024